Petroleum source rock properties of the Neogene Bhuban shales,Bengal Basin, Bangladesh - Md. Farhaduzzaman; Wan Hasiah Abdullah; Md. Aminul Islam (Universiti Kebangsaan Malaysia, 2015)
The present study evaluates the petroleum source rock generation potential of the Neogene Bhuban shales from Bangladesh. Organic geochemical and organic petrological methods were used for analyzing 11 drill core samples from 4 gas fields in the basin. Source rock potential, maceral composition, organic matter abundance, biomarker distribution, thermal maturity, hydrocarbon generation and depositional environment were evaluated. Kerogen in the studied shale samples is classified mainly as Type III with lesser amounts of Type II. Vitrinite is the dominant maceral group observed in the analyzed Bhuban samples followed by liptinite and inertinite. Vitrinite reflectance, Tmax and biomarker parameters indicate the thermal maturity ranges from just pre-oil window to mid-oil window. Based on its total organic carbon (TOC), extractable organic matter (EOM) and hydrogen index (HI), the analyzed Bhuban shales are ranked as mainly poor to fair source rocks but with good gas generation potential. The dominant terrestrial environment prevailed during the deposition of the studied Bhuban shales while the condition was sub-oxic as indicated by cross-plots of pristane versus phytane and sterane versus pristane/phytane ratios.